Current Anatolian Water Buffalo (Bubalus bubalis) Husbandry Practices at Igdir Province, Turkey - Isa YILMAZ; Onur SAHİN; Mabrouk ELSABAGH (ISPEC Journal of Agricultural Sciences)
This study was conducted as a survey study in the 2017 (from September to December) to analyze the current status and husbandry practices of Anatolian water buffalo enterprises in Igdir, Turkey. Using the Simple Random Sampling procedure, a sample of 98 enterprises was selected among 319 Anatolian water buffalo producers to apply a questionnaire as a primary source of data collection. The data revealed that the average age of the owners was 56.87±1.27 years and they are literate and have mixed enterprises. The first age of the breeding of buffalo, postpartum service internal, insemination after estrus detection, lactation length and the number of inseminations per gestation were 28.20±0.67 months, 72.47±2.82 days, 2.91±0.23 hours, 236.74 days and 1.29±0.06 times, respectively. The average intake time of first colostrum, the amount of milk intake within the first two hours after birth and the weaning age in the Anatolian water buffalo calves were 1.59±0.72 hours, 2.71±0.97 kg and 208.42±48.25, respectively. Implementation of effective policies to develop the breeding of Anatolian water buffalo in Igdir is mandatory. Such policies include extension services (on nutrition, veterinary care, product processing…etc.), increasing the herd numbers, and establishing a union for Anatolian Water Buffalo Breeders in Igdir province.